Drivers and determinants of extreme humanitarian needs among Rohingya refugee households: Evidence from UNHCR’s multi-sectoral needs analysis - Harry Wilson (PLoS ONE, 2025)
Background The Rohingya refugee crisis continues to deteriorate amid major funding cuts and a myriad of intensifying threats. Approximately one million Rohingya refugees are currently housed within 33 densely populated camps in Cox’s Bazar, Bangladesh. This study aimed to estimate the prevalence of households in extreme humanitarian need, identify sector-specific drivers, and elucidate household characteristics associated with extreme humanitarian needs to strategically inform humanitarian relief efforts. Methods Data were sourced from the 2023 Joint Multi-Sectoral Needs Assessment (J-MSNA) – a representative cross-sectional survey of Rohingya refugee households. Households were selected via stratified simple random sampling from UNHCR’s database of registered refugees. Data were collected from 3,400 households and 18,172 household members distributed across the 33 camps of Cox’s Bazar through face-to-face interviews using a pre-tested structured questionnaire between August and September 2023. Survey-adjusted logistic regression was used to elucidate household characteristics associated with extreme humanitarian needs. Results A total of 1,206 households (35.5%) were found to be in extreme humanitarian need, predominantly driven by sector-specific needs within the education (17.2%), food security (12.7%), and health sectors (7.2%). In adjusted analysis, household characteristics significantly associated with increased odds of extreme humanitarian needs included female head of households (aOR = 1.65, 95% CI = 1.29–2.12), head of household age between 30–49 years (aOR = 1.58, 95% CI = 1.27–1.96), or age 50 and older (aOR = 2.18, 95% CI = 1.74–2.72), increasing household size (aOR = 1.20, 95% CI = 1.15–1.25), and households with at least one member experiencing symptoms of psychosocial distress or trauma (aOR = 1.25, 95% CI = 1.06–1.46). Conclusion The findings attest to the deteriorating Rohingya refugee crisis in Cox’s Bazar. The household characteristics associated with extreme humanitarian needs highlight the repercussions of contemporary funding cuts among vulnerable cohorts that pay the heaviest price. The resurgence of targeted violence in Myanmar and intensity of the protracted crisis in Bangladesh demands a more compassionate and enduring humanitarian response from the international community.